1994
DOI: 10.1128/mcb.14.2.989
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the DNA-binding activity of c-jun/c-fos heterodimers by the hepatitis B virus transactivator pX.

Abstract: (13,28,42,49,55) and cellular (10,23,27,47,56) Phosphorylation and dephosphorylation of c-Fos and c-Jun have been described as posttranslational modifications with a critical role in the regulation of AP1 function. Phosphorylation of the c-Fos C terminus seems to be important for negative autoregulation and for transformation (34,46) but not for transactivation of genes linked to an AP1 site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 36 publications
2
100
0
1
Order By: Relevance
“…On the other hand, most tumors contain clonally integrated HBV DNA and microdeletions in the flanking cellular DNA which could, theoretically, deregulate cellular growth control mechanisms. 86 Furthermore, the HBV X gene product has been shown to transactivate cellular genes associated with cellular growth control [87][88][89] and inhibit p53 gene function in vitro 90 , suggesting that deregulated X gene expression from integrated fragments of subviral DNA could play a role in hepatocarcinogenesis. 91 Similarly, C-terminally truncated viral envelope proteins expressed from integrated subviral DNA may have transactivating activity 92,93 and could, potentially, contribute to carcinogenesis in chronic HBV infection.…”
Section: Immune Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“…On the other hand, most tumors contain clonally integrated HBV DNA and microdeletions in the flanking cellular DNA which could, theoretically, deregulate cellular growth control mechanisms. 86 Furthermore, the HBV X gene product has been shown to transactivate cellular genes associated with cellular growth control [87][88][89] and inhibit p53 gene function in vitro 90 , suggesting that deregulated X gene expression from integrated fragments of subviral DNA could play a role in hepatocarcinogenesis. 91 Similarly, C-terminally truncated viral envelope proteins expressed from integrated subviral DNA may have transactivating activity 92,93 and could, potentially, contribute to carcinogenesis in chronic HBV infection.…”
Section: Immune Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“…Several reports indicated that HBx induces activation of the transcription factor activator protein-1 (AP-1), a dimer consisting of Fos and Jun proteins; however, it does not accomplish this through a direct interaction. [101][102][103][104][105][106] This led to the discovery that HBx increases the activation of Ras, a GTP-binding protein which lies upstream in the MAPK signaling cascade. As shown in Fig.…”
Section: Ras-raf-mapkmentioning
confidence: 99%
“…1A). Comparable amounts of proteins were applied and fractionated by SDS-PAGE as shown by Coomassie Blue staining (lanes [25][26][27][28][29][30]. The RPB5 probe bound to TFIIB with high affinity (lane 2) as well as to HBx and to itself as reported (lanes 4 and 6) (18).…”
Section: Hbx Rpb5 and Tfiib Associate With Each Other In Vitro And mentioning
confidence: 99%